Role of Serum ß-Carotene in the Diagnosis and Prevention of Oral Squamous Cell Carcinoma – A Case Control Study - Chippagiri, Prashanthi (JCDR Research and Publications (P) Limited, 2014)
Context: Oral squamous cell carcinoma (OSCC) is the most common cancer of the head and neck. It accounts for more than 90% of all malignancies Which occur in the head and neck region. The high incidence and mortality rate of oral cancer stimulates continuation of research on finding new diagnostic tools or markers for it. Aim: To evaluate the possible role of serum β-carotene as a biochemical parameter in the diagnosis of oral squamous cell carcinoma. Materials and Methods: The serumβ-carotene levels in 40 patients with clinically diagnosed and histopathologically confirmed oral squamous cell carcinoma were estimated and the levels were compared with those of 40 healthy controls. The serum β-carotene levels were estimated by using a spectrophotometer. The data which was obtained was analyzed statistically by using unpaired t-test. Results: Subjects with oral squamous cell carcinoma showed significantly lower levels of mean serum β-carotene (149.95 ± 61.29) as compared to those seen in controls (278.19 ± 90.12). Conclusion: The results of the present study are encouraging and they suggest that the estimation of the low levels of β-carotene in the patients with oral squamous cell carcinoma may be a useful diagnostic tool for making the diagnosis of oral squamous Cell carcinoma and thereby improving the prognosis of this dreaded disease.